Circadian Clock Protein Content and Daily Rhythm of Locomotor Activity Are Altered after Chronic Exposure to Lead in Rat - Sabbar, Mariam; Dkhissi-Benyahya, Ouria; Benazzouz, Abdelhamid; Lakhdar-Ghazal, Nouria (Frontiers in Behavioral Neuroscience, 2017)
Lead exposure has been reported to produce many clinical features, including parkinsonism. However, its consequences on the circadian rhythms are still unknown. Here we aimed to examine the circadian rhythms of locomotor activity following lead intoxication and investigate the mechanisms by which lead may induce alterations of circadian rhythms in rats. Male Wistar rats were injected with lead or sodium acetate (10 mg/kg/day, i.p.) during 4 weeks. Both groups were tested in the “open field” to quantify the exploratory activity and in the rotarod to evaluate motor coordination. Then, animals were submitted to continuous 24h recordings of locomotor activity under 14/10 Light/dark (14/10 LD) cycle and in complete darkness (DD). At the end of experiments, the clock proteins BMAL1, PER1-2 and CRY1-2 were assayed in the suprachiasmatic nucleus (SCN) using immunohistochemistry. We showed that lead significantly reduced the number of crossing in the open field, impaired motor coordination and altered the daily locomotor activity rhythm. When the LD cycle was advanced by 6h, both groups adjusted their daily locomotor activity to the new LD cycle with high onset variability in lead-intoxicated rats compared to controls. Lead also led to a decrease in the number of immunoreactive cells (ir-) of BMAL1, PER1 and PER2 without affecting the number of ir-CRY1 and ir-CRY2 cells in the SCN. Our data provide strong evidence that lead intoxication disturbs the rhythm of locomotor activity and alters clock proteins expression in the SCN. They contribute to the understanding of the mechanism by which lead induce circadian rhythms disturbances